PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH-SEKOLAH MENENGAH KEJURUAN (SMK) YAYASAN YOHANNES GABRIEL PERWAKILAN IV SUB PERWAKILAN MADIUN - Kusumasari, Nurmala Afifah; Widiatna, Alexius Dwi (CREDENDUM: Jurnal Pendidikan Agama, 2022)
Vocational High School Education (VHS) emphasizes practice in the implementation of learning because it prepares students for work. Principals of vocational schools need teacher collaboration to improve the quality of education. Research method used is quantitative research method. The population on the research are teachers who work at Vocational High School under the auspices of the fourth representative of John Gabriel foundation. The sample for this research is 47 teachers. Sample selection method for this research use simple random sampling. Variable independent on this research is principals democratic leadership style, and variable dependent on this research is teacher performance. Linearity test concluded that there are linear relationship significant among principals democratic leadership style (X) variable with teacher performance (Y). The data analysis show that there are a significant and linear relationship between the principal's democratic leadership style with teacher performance. The results of the research, it was found that the democratic leadership style of the principal has a linear relationship to teacher performance and has a significant impact on the performance of VHS teachers at the fourth representative of John Gabriel foundation.